Mandibular fracture in a neonate. Issue 1 (January 2017) - Gopalakrishnan, V.; Sahoo, N.K.; Roy, I.D.
Abstract: Mandibular fractures in the neonate are rare. The aetiological factors are traumatic delivery, accidental fall, road traffic accidents, and attempted infanticide. The diagnosis is difficult due to facial oedema masking the clinical features and the absence of dentition. The treatment of fractures in the newborn represents a unique problem in terms of investigations, diagnosis, selection of anaesthesia, and method of fixation. The case of a 1-day-old infant referred for the management of a mandibular fracture sustained in an accidental fall is presented herein. During oral suctioning, the neonatologist observed continuous blood-stained secretions, which raised the suspicion of a trauma to the oral cavity. The infant was diagnosed as having a fracture of the mandibular symphysis with displacement. The fracture was reduced under local anaesthesia with sedation, and was stabilized with an acrylic splint, which was secured with circum-mandibular wiring. The patient was followed up for 1.5 years and the healing was satisfactory.